INFLUENCE OF DFOLIATION METHODS AND STANDING DENSITY OF PLANTS ON THE ACCUMULATION OF DRY MASS OF SOYBEAN VARIETIES (Conferencea, 2023)
This article presents the results of an experiment on the effect of seedling thickness and defoliation rates on the accumulation of dry mass of soybean varieties sown as a repeated crop.